PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP HUBUNGAN ANTARA GAYA KEPEMIMPINAN DENGAN KINERJA AUDITOR (Studi Empiris di KAP DIY) - Septiyani Putri Astutik (Journal Competency of Business, 2017)
Auditor’s performance is an important factor in wich determine quality of CPA firm. This made CPA firm need to improve their performance. Therefore this research analyses leadership style influence to auditor’s performance. This research also analyses the effect of organizational commitment and job satisfaction to relation between leadership style and auditor’s performance.The sampling technique applied is purposive sampling and research data is primary data colected by sending questionaire direct in various CPA firm in Yogyakarta. This research utilizes 48 junior auditor of 5 CPA firm in Yogyakarta. Test hypotesis done by using linear regression and Moderatde Regression Analysis (MRA). Result this research proved that leadership style affect the auditor’s performance significantly. This research also shows that organizational commitment cannot moderation relation between leadership style and auditor’s performance. For job satisfaction, this result proved that job satisfaction can moderation realtion between leadership style and auditor’s performance, but with negative affect.